Causal association of polyunsaturated fatty acids with chronic pain: a two-sample Mendelian randomization study - Dai, Yuxuan; Chen, Yu; Gu, Rui; Zhang, Chao; Jiang, Rui (Frontiers in Nutrition, 2023)
Observational studies have indicated an association between polyunsaturated fatty acids (PUFAs) and chronic pain, but the potential causal link remains controversial.Here, we aimed to investigate whether a causal relationship exists between the concentration of circulating PUFAs and chronic pain as well as the direction of this association. We collected statistical data from relevant genome-wide association studies to explore the causal link between four PUFAs, along with the ratio of omega-6 fatty acids (FAs) to omega-3 FAs (omega-6:3 ratio), and chronic pain in eight specific body parts. We used the inverse-variance weighting (IVW) method for two-sample Mendelian randomization (MR) analysis and conducted supplementary analyses using four other methods (MR-Egger, weighted median, weighted mode, and simple mode).To verify the robustness of the MR study, we performed multiple sensitivity analyses.The results revealed a negative correlation between omega-3 FAs [IVW, OR 95% CI: 0.952 (0.914, 0.991), P=0.017] and docosahexaenoic acid (DHA) [IVW, OR 95% CI: 0.935 (0.893, 0.978), P=0.003] with abnormal and pelvic pain. Furthermore, a positive correlation was observed between the omega-6:3 ratio [IVW, OR 95% CI: 1.057 (1.014, 1.101), P=0.009] with abdominal and pelvic pain. Additionally, we found a negative correlation between omega-3 FAs [IVW, OR 95% CI: 0.947 (0.902, 0.994), P=0.028] and lower back pain or sciatica. However, no causal relationship was found between the concentration of circulating PUFAs and pain in other body parts, including the face, throat and chest, joints, limbs, lower back, and gynecological parts. The robustness of these MR results was verified through multi-validity and retention method analyses.Our analysis suggests that higher circulating concentrations of omega-3 FAs and DHA and a lower omega-6:3 ratio are associated with a reduced risk of abdominal and pelvic pain. Additionally, a higher concentration of circulating omega-3 FAs is linked to a reduced risk of lower back pain and/or sciatica. These findings have major implications for the targeted prevention and treatment of chronic pain using PUFAs.